Personality dimensions as determinants of breast cancer progression and quality of life - Ali Talaei; Fatemeh Homaei Shandiz; Elham Ghaffari; Asma Khorshi Shamshiri; Sahar Omidvar-Tehrani; Fahimeh Afzaljavan (Middle East Current Psychiatry)
Abstract Background Patients newly diagnosed with breast cancer often experience varied psychosocial responses and treatment outcomes, potentially influenced by personality traits. Understanding these traits can help clinicians predict psychological reactions and tailor early psychiatric or psychological interventions. This study examines the link between personality dimensions, breast cancer prognosis, and quality of life. Methods In a comparative cross-sectional study conducted in Northeast Iran, 130 breast cancer patients and 158 healthy individuals completed demographic and Cloninger Temperament and Character Inventory questionnaires. Patients also completed the EORTC QLQ-BR23 quality of life questionnaire. Clinical data and progression-free survival were obtained from medical records. Data analysis was conducted using SPSS v16. Results Breast cancer patients had significantly higher self-transcendence scores than the healthy group (p < 0.001, effect size = 7%). High cooperativeness (p = 0.008) was higher in patients, whereas low harm avoidance (p < 0.001), novelty seeking (p = 0.013), persistence (p = 0.012), and self-transcendence (p = 0.021) were lower compared to controls. Additionally, global health was significantly lower in low reward dependency (p = 0.018, effect size = 6%) and persistence (p = 0.005, effect size = 8%) than normal scores. Survival analysis indicated that high harm avoidance was associated with an elevated hazard rate [p = 0.033, HR = 4.72, 95%CI (1.14–19.58)], whereas high self-transcendence correlated with a reduced hazard rate of disease progression [p = 0.015, HR = 0.27, 95%CI (0.09–0.77)]. Conclusion Personality traits significantly influence breast cancer progression and quality of life. The study highlights the potential for integrating early psychological risk assessments and personalized psychotherapy interventions to enhance the psychological well-being of breast cancer patients, offering a proactive approach to supportive care.